Hydrogen Peroxide Treatment of Natural Lake Sediment Prior to Carbon and Oxygen Stable Isotope Analysis of Calcium Carbonate - Georgina Falster; Steven Delean; Jonathan Tyler (Geochemistry, Geophysics, Geosystems, 2018)
Abstract The carbon and oxygen stable isotope ratios (δ13C and δ18O) of authigenic and biogenic lacustrine carbonates are commonly used as past climate proxies, and these carbonates are often preserved within organic‐rich bulk sediment. We measured the δ13C and δ18O of carbon dioxide evolved from fine‐grained crystalline calcite and biogenic aragonite, mixed with natural organic‐rich lake sediment. We found that if the ratio of total inorganic carbon (TIC) to total organic carbon (TOC) in lacustrine bulk sediment is low, then organic compounds evolve detectable CO2 during phosphoric acid digestion, leading to an “organic bias” in the measured δ13C and δ18O. We tested the effect of oxidative pretreatment of the bulk sediment with acidic or alkaline hydrogen peroxide (H2O2), at a range of temperatures. Pretreatment with acidic H2O2 not only had a negligible effect on the TIC/TOC but also resulted in dissolution and reprecipitation of carbonate, and a consequent “treatment bias” that was particularly strong for δ18O. Oxidation with alkaline H2O2 removed a greater proportion of organic material, with no evidence for carbonate dissolution at temperatures of ≤50 °C. The δ13C and δ18O values obtained from sediment treated with alkaline H2O2 at 50 °C were both accurate and precise, even for sediment with very low initial TIC/TOC. Our results show that it is possible to obtain accurate δ13C and δ18O values from carbonates preserved within organic‐rich lacustrine sediment, suitable for use in paleoclimate reconstructions.